2010
DOI: 10.1136/adc.2009.174433
|View full text |Cite
|
Sign up to set email alerts
|

Two-year neurodevelopmental outcome of preterm born children <=750 g at birth

Abstract: Increased survival of infants with a birth weight ≤750 g coincided with more children with an impaired NDO at 2 years corrected age. SGA infants are especially at risk of impaired NDO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 50 publications
4
36
1
Order By: Relevance
“…By contrast, Matilainen et al reported that both gross and fine motor skills were more impaired in SGA children (14). Other studies have also reported increased incidences of spastic motor outcomes and gross motor impairment (15,16). Of note, in our study motor skills were observed to be affected in as many as ~50% of the children in both the SGA and AGA groups.…”
Section: Discussioncontrasting
confidence: 42%
“…By contrast, Matilainen et al reported that both gross and fine motor skills were more impaired in SGA children (14). Other studies have also reported increased incidences of spastic motor outcomes and gross motor impairment (15,16). Of note, in our study motor skills were observed to be affected in as many as ~50% of the children in both the SGA and AGA groups.…”
Section: Discussioncontrasting
confidence: 42%
“…Study participants were assessed between the ages of 18 and 40 months using the BSID in 13 studies, the Griffiths Mental Development Scales in 6 studies, the Stanford-Binet Intelligence Scale in 1 study, and the Brunet-Lezine Scale in 1 study. In 3 studies, 16,23,29 >1 of these assessment tools were used. School-age cognitive assessments were conducted between the ages of 5 and 18 years, and 11 different tests were used.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 The obstetrician's willingness to intervene on fetal behalf was associated with lower stillbirth rates and improved survival in infants weighing ,1000 g but was also associated with major neonatal morbidity. 16 Approximately 25% of EPT infants born in the 1990s had a major neurodevelopmental disability at preschool age 20 ; since then, decreasing, 21 unchanged, 22,23 or increasing 19,24,25 rates of neurodevelopmental impairment (NDI) have been reported. Few studies, however, have examined outcomes after explicitly proactive care, 6,15,26 and stillbirths are seldom included in outcome studies.…”
Section: What This Study Addsmentioning
confidence: 99%